Women Oppression as a Result of Male Dominated Culture as Represented in Shenoy’s Novel ‘The Secret Wish List’ - Dwi Astuti Ratna (EDP Sciences, 2021)
Oppression is the name of social injustice. It is perpetuated through social institutions, practices, and norms on the social group by social group. Indian society belongs to the man since a long time ago Indian woman has been given a secondary and inferior position in family and society. She has faced injustice, suppression, oppression, subjugation, and exploitation in a male-dominated Indian society. It has been worst because of the Covid-19 pandemic. This study describes how male domination and woman’s oppression is experienced by an Indian woman and its explanation to what extent women reject male domination represented in The Secret Wish List novel by Preeti Shenoy. The method used in this study is a descriptive qualitative study and uses Derrida’s theory of deconstruction to support the data. The main theory used in this study is Simone de Beauvoir’s theory of Existentialist Feminism. This study shows that the novel deconstructs its portrayal of male domination towards women. So, by destabilizing the binary opposition in the novel, that are males oppose females, the males-females hierarchy are reversed.